Determinants Of Stunting Incidence In Toddlers In Pasaman Barat - Siti Nur Azizah; M. Ridwan; Puspitasari (International Journal of Health Engineering and Technology, 2024)
The incidence of stunting in Indonesia in 2021 is relatively high with a stunting prevalence of 24.4%, and one area in West Pasaman Regency has even experienced an increase in the incidence of stunting in 2022. The adverse effects of stunting are not only related to the child's height, it can also cause permanent disability and affect the child's future. To find out the factors associated with the incidence of stunting in toddlers.this research is a quantitative study with an observational analytic design through a cross-sectional approach. The sample is taken by simple random sampling technique. Data processing is in the form of univariate analysis and bivariate analysis. The results of the data analysis in this study obtained significant results between the incidence of stunting and parenting factors and economic factors. various factors include causing the incidence of stunting in toddlers in West Pasaman Regency, so that family assistance is one of the efforts to prevent stunting incidents.